Clinical outcomes and cost-effectiveness of collaborative treatment with Korean and Western medicine in patients with facial palsy: a multicenter prospective observational study - Shiva Raj Acharya; Linae Kim; NamKwen Kim (BMC Complementary Medicine and Therapies)
Abstract Background Effective and cost-efficient treatment approaches are crucial in healthcare to optimize patient outcomes. This study evaluates and compares the clinical outcomes and cost-effectiveness of Korean and Western medicine collaborative treatment (CT) with usual care (UC) for patients with facial palsy (FP). Methods A two-arm comparative, multicenter, prospective, observational study was conducted at 11 nationwide hospitals participating in the fourth phase of the national pilot project for CT. A total of 130 FP patients were enrolled at baseline, with follow-up assessments at 4 weeks and 12 weeks post-baseline. Clinical outcomes were evaluated using the House-Brackmann Grading Scale (HBGS), Numeric Rating Scale (NRS), EuroQol-5 Dimensions (EQ-5D-5L), and EuroQol-Visual Analogue Scale (EQ-VAS) at all three time points of the study. The cost-effectiveness evaluation was assessed using Cost per QALYs (Quality-Adjusted Life Years), Incremental Cost-Effectiveness Ratio (ICER), and Net Monetary Benefit (NMB). Results The mean HBGS, NRS and EQ-VAS scores significantly improved in both groups over time (each, p < 0.05). Compared to UC, CT demonstrated significantly higher EQ-5D-5L scores (0.94 ± 0.11 vs. 0.91 ± 0.13), and this effect remained significant even after adjusting for age, sex, duration, and income level (β = 0.06, p < 0.05). From a limited societal perspective, the total cost difference between the two groups was not statistically significant; however, the QALYs gained were significantly higher in patients who received CT than those who received UC (0.010 QALYs vs. 0.008 QALYs). The ICER for CT was estimated at 28.1 million Korean Won (KRW) per QALY. The probability that CT would be more cost-effective than UC exceeded 50% at a WTP threshold of 30.5 million KRW per QALY. Conclusions Our study highlights that CT enhances a better quality of life and is more cost-effective for FP treatment, suggesting it is a valuable alternative to usual care. Further large-scale clinical trials and cost-effectiveness studies are warranted to explore its broader application and validate these findings. Trial registration The study design was registered with the Clinical Research Information Service (CRIS) of South Korea at https://cris.nih.go.kr/ (KCT0007682) on September 07, 2022.